ALOKASI DANA DESA DALAM PERSPEKTIF AKUNTANSI DAN KEUANGAN - Marvanti, Iga Vidya; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the implementation of accounting and financial management, thedisbursement mechanism, the preparation stages of financial management, problems which are encountered inthe implementation of accounting and financial management of village allocation fund and the efforts which havebeen carried out in order to overcome the problems which occur at Medaeng village in Waru district in Sidoarjoregency. This research is a descriptive researtch which has been carried out by using qualitative approach. Thesources of data are the primary and the secondary data. The data collection technique has been conducted in theform of observation, interview, library research, and documentation. The result of data collection is analyzed byusing comparative qualitative descriptive method. The result of the research shows that the financial accountingsystem of village allocation fund has been carried out by using microsoft excel program in the form of generalcash book and cash book helpers of receipts and cash book helpers of expenditure. Meanwhile, the financialmanagement in 2015 was quite well and realistic since it has been prepared in budget